Child Maltreatment: Neglect of Child Welfare After Sexual Violence - Syahrul Akmal Latif; Riky Novarizal (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The treatment of children receives after experiencing sexual abuse incidents often results in acts of child maltreatment from the family, community, and school. This child maltreatment indicates that there has been a neglect of the well-being of children after experiencing sexual abuse incidents. This study aims to explain and analyze cases, treatment, and conditions in a group of girls after experiencing sexual abuse incidents. Because so far there are only a few studies that pay special attention to the condition of children after experiencing sexual abuse incidents. This study is descriptive qualitative. Data collection was carried out through the process of reading online news using the search keyword "Sexual abuse against children in Indonesia" through the Google search engine. This study shows that the child maltreatment that children receive after experiencing sexual abuse incidents appears in the form of expulsion of children from their homes, being dismissed from school, and being forced to marry the perpetrators. This context is clear evidence that the welfare of children after experiencing sexual abuse incidents has been ignored by their social communities. This study also recommends the importance of comparative studies of cases, treatment, and conditions of children after experiencing sexual abuse incidents by interviewing groups of girls and boys who are more empirical.